Influence of digestible protein levels on growth and feed utilization of juvenile meagre Argyrosomus regius. (22nd May 2014) - Velazco‐Vargas, J.; Tomás‐Vidal, A.; Hamdan, M.; Moyano López, F.J.; Jover Cerda, M.; Martínez‐Llorens, S.
Abstract This study investigates the effect of digestible protein levels in experimental diets for meagre (Argyrosomus regius). A group of 253 fish, 52 g of mean weight, was distributed in 12 tanks, three replicates per treatment. Four isolipidic diets (170 g kg−1 crude lipid) with different digestible protein levels (350 g kg−1, 430 g kg−1, 490 g kg−1 and 530 g kg−1) were formulated using commercial ingredients. The trial lasted 62 days. Meagre fed diets 430, 490 and 530 g kg−1 obtained higher TGC (2.47, 2.57, 2.69 × 10−3, respectively) than fish fed diet 350 g kg−1 (2.14 × 10−3). Group of fish fed diet with 350 g kg−1 DP showed the lowest ammonia excretion level. According to the in vitro digestibility trial diets with 350 and 430 g kg−1 DP released less amino acids in comparison with diet with 49% DP, although in vivo digestibility test did not show significant differences among diets 430, 490 and 530 g kg−1 DP. Using the quadratic regression, optimal digestible protein intake according to the ECR for rearing juvenile meagre was recorded in 0.8 g DP/100 g fish and day.